THE INFLUENCES OF VISIONARY LEADERSHIP ON THE INTERNATIONAL COOPERATION IN ART EDUCATION MANAGEMENT IN HIGHER EDUCATIONAL INSTITUTIONS, LIAONING PROVINCE, CHINA - Xiaoting, Sun; Senarith, Prapatpong; Moonmuang, Sukhoom (วารสารวิจัยธรรมศึกษา, 2022)
To keep up with the fast-changing globalized economy and challenging government policies, higher education system in China has been demanded to accordingly strengthen its operation, so as to upgrade the nation’s human resources with proper mindset and skills. The objectives of this research were: (1) To identify the status of international cooperation in art education management in higher educational institutions in Liaoning Province, China; (2) To identify influencing factors on the international cooperation; (3) To analyze the relationships among those influencing factors identified. and (4) To evaluate the models fit. The research methodology used was quantitative survey research. A total of 380 art teachers working in 15 public colleges and universities in Liaoning Province, China, in the academic year 2021 were selected, by using multi-stage random sampling, as samples for this study. A semi-structured self-rating questionnaire was used to collect data. The data analyses employed included frequency, percentage, mean, standard deviation, path analysis, and structural equations modelling. The research findings revealed that: (1) The international cooperation in art education management in colleges and universities in Liaoning Province was highly perceived by art teachers; (2) Except teachers’ willingness, the influencing factors of international cooperation included visionary leadership, organizational reputation, and teachers’ organizational commitment; (3) Visionary leadership significantly exerted its influences on international cooperation both directly and indirectly via organizational reputation.; and (4) The models under study fitted the empirical data well.